Mangkunegaran Temple as A Leading Cultural Tourism Attraction: an Analysis Of Digital Marketing Integration and Heritage Preservation in Solo City - LAHAGU, Agusman; PRANOTO, Pranoto (Journal of Tourism Economics and Policy, 2025)
This research analyzes Pura Mangkunegaran as a leading cultural tourism attraction in Solo City with a focus on digital marketing integration and cultural heritage preservation. Using a qualitative approach with a case study method, data was collected through in-depth interviews with 15 informants, participatory observation, and Instagram social media analysis. The results showed that Pura Mangkunegaran has a very high cultural tourism potential with 268 years of historical value, a collection of 5,000 artifacts, and original Javanese-European architecture. The visitation rate reached 132,060 people in 2024 with 300% growth from the previous year. A digital marketing strategy through Instagram @mangkunegaran with 65,000 followers proved effective in increasing awareness and visitation. Key challenges include limited digital infrastructure, content inconsistency, and a gap between tradition and millennial traveler expectations. This research recommends an integrated strategy that combines digitization of cultural heritage, interactive content development, and strengthening stakeholder partnerships to make Pura Mangkunegaran a major attraction for sustainable cultural tourism in Indonesia.